As influências das garantias de ficção, literária e de uso na indexação da literatura infantojuvenil: proposta de modelo de leitura - Vesu Alves, Roberta Caroline (2020)
The fiction, literary, and user warranties were verified in order to observe if they base the elaboration of a documentary reading model for indexing fictional narrative text in prose, in the aspects of subject identification, selection and representation. The methodology consisted of bibliographic research and exploratory study, with qualitative analysis for the development of documentary reading model, which was evaluated by school librarians through the methodology of individual verbal protocol to verify and improve the model. As results, warranties of fiction, literary and use contribute to foundation of documentary reading model for indexation of literature for children and adolescents as observed in the model evaluation. Some aspects of model had to be improved. Important text elements for representation and retrieval of information by users are related to warranties and were evidenced by characters, action or event, space, time, theme or subject, narrator, literary genres, educational themes from author's point of view and some cognitive aspects of reader. The empirical model of documentary reading was based on warranties and was important for indexing by school librarians, who approved of applying the model and showed ways to improve.